ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¹Ù„Ù‰ Ø¶ÙˆØ¡ Ø§Ù„Ø°ÙƒØ§Ø¡Ø§Øª Ø§Ù„Ù…ØªØ¹Ø¯Ø¯Ø© (Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ØØ§Ù„Ø© ÙÙŠ Ù…Ø¯Ø±Ø³Ø© Ù…Ø§Ù„Ùƒ Ø¥Ø¨Ø±Ø§Ù‡ÙŠÙ… Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø¨ÙƒØ±Ø³ÙŠÙƒ) - Saiul Anah (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2023)
There are three objectives of this research: 1) to know the learning of learning the Arabic language based on the multiple intelligences of Gifted students at Malik Ibrahim Junior High School of Gresik, 2) to know the dominant types of multiple intelligences in learning the Arabic language at Malik Ibrahim Junior High School of Gresik, and 3) to know the benefits of Multiple Intelligences in learning the Arabic language for Gifted students at Malik Ibrahim Junior High School of Gresik. The researcher applied a qualitative approach namely case study method. The data collected is taken from recording observation and interview and is analyzed by interactive model analysis. Substantive findings consist of: (a) the Varieties of learning models arabic language base on the multiple intelligences at Malik Ibrahim Junior High School of Gresik is multiple model and interdisipliner for learning activity. 2) Technique of Multiple Intelligences in learning the Arabic language : a) question and answer Technique. There is two varieties of discussion: closing question (some ask there is a question) and opening question (many answering). b). Speech Tehnique. Speech tehnique is interdisipliner for learning activity every week get a student to speech with tittle in arabic book. c). Discussion Tehnique 3) Multiple Intelligences have some benefits for each learning is motivation, customisation learning and easy for learning activity. The formal research findings showed that learning multiple for multiple intelligence can give impact student for Motivation dan customisation for student intelligent appropriation.